Welfare, Populism and Welfare Chauvinism - Greve, Bent; Greve, Bent (Book collections on Project MUSE., 2019)
In the wake of the financial crisis, and with increasing numbers of people in precarious and low paid jobs, there has been a surprising surge of support for populist right-wing political parties who often promote an anti-welfare message. Tougher approaches and welfare chauvinism is on the agenda in many countries, with policies which reduce the welfare state for those seen as undeserving and changes that often disproportionally benefit the rich. Why are voters seemingly not concerned about growing inequality? Using a mixed methods approach and newly released data, this book aims to answer this question and to show possible ways forward for welfare states.